Research on prevention and treatment of elderly type 2 diabetes based on the combination of medical and nursing care mode - Li Rui; Fredie Robinson (Frontiers in Health Informatics Publications, Ghaziabad, Uttar Pradesh, India, 2024)
Objective: This study aims to analyze the current status of elderly care services and medical assistance for the elderly, and to delve into the actual medical service needs of the elderly under the combined medical and nursing care mode. Furthermore, it investigates whether this mode helps reduce the incidence of complications in patients with type 2 diabetes mellitus (T2DM) and whether it can effectively improve key health indicators (such as fasting blood glucose, triglyceride, glycated hemoglobin, and urine microalbumin levels) among elderly diabetic patients, thereby enhancing their quality of life. Additionally, this study explores the differences in satisfaction among T2DM patients at the end-of-life stage under the combined medical and nursing care mode, constructs relevant mode and questionnaires, lays a foundation for the clinical application and management of chronic diseases in the elderly, and promotes the development of prevention and treatment efforts for chronic diseases in the elderly in China. Methods: The study initially established a control group and an prevation group, measured and compared baseline indicators between the two groups, and analyzed the correlation between fasting blood glucose, triglyceride, glycated hemoglobin, microalbuminuria, and factors such as age and weight. Subsequently, treatment interventions were administered to both groups separately in three hospitals. After routine treatment, a t-test was employed to compare treatment outcomes between the control and prevation group by gender, and the correlation between the aforementioned indicators and age, weight was re-measured and analyzed. Finally, differences in measurement indicators were compared within the control group and between the control and prevation group at two time points. Results:The research findings demonstrate that the combination of medical nursing care mode excels in optimizing fasting blood glucose management among type 2 diabetes patients. Specifically, this mode significantly reduced patients' fasting blood glucose levels, glycated hemoglobin concentrations, triglyceride levels, and urinary microalbumin content. After six months of treatment, both the mean and median of the baseline data showed a decline, indicating the remarkable efficacy of the combination of medical nursing care mode in controlling fasting blood glucose among type 2 diabetes patients. The specific data are as follows: fasting blood glucose (mean = 7.826±0.135), glycated hemoglobin concentration (mean=6.480±0.789), triglycerides (mean=1.553±0.066), and urinary microalbumin (mean=12.869±0.426), all of which were lower than the control group and significantly different from the initial baseline measurements. Over the six-month treatment period, the Mann-Whitney U test revealed more pronounced reductions in the mean and median of baseline data in the intervention group compared to the control group. From the index value of the prevation group of body weight, fasting blood glucose, triglyceride, glycosylated hemoglobin and urinary microalbumin, and there were significant differences in the conventional treatment effect of each hospital. Specifically, the intervention group showed greater mean differences in fasting blood glucose (1.867±0.277), glycated hemoglobin concentration (1.782 ±0.164), and triglycerides (0.761±0.094) compared to the control group. Furthermore, a statistically significant difference was observed in fasting blood glucose between the two groups. According to data of the first measurement of the two groups, There was a positive correlation between glycosylated hemoglobin and Fasting blood glucose（r=0.224，p=0.001）in the control group. According to data, there was a positive correlation between glycosylated hemoglobin and weight（r=0.228，p=0.001）in the prevation group. There was also a positive correlation between urinary microalbumin and fasting blood glucose（r=0.193，p=0.002）in the prevation group. Conclusion: In conclusion, the comprehensive combination of medical nursing care mode has demonstrated significant therapeutic effects in reducing fasting blood glucose, glycated hemoglobin, triglycerides, and urinary microalbumin levels in patients with type 2 diabetes.